"Green" ethers as solvent alternatives for anionic ring-opening polymerizations of ethylene oxide (EO): In-situ kinetic and advanced characterization studies. (20th December 2018) - Majdanski, Tobias C.; Vitz, Jürgen; Meier, Alexander; Brunzel, Michaela; Schubert, Stephanie; Nischang, Ivo; Schubert, Ulrich S.
Abstract: In the present work, the polymerization process of ethylene oxide (EO) leading to diphenyl-PEO-OH with a molar mass of 5000 and 10, 000 g mol −1 in different ethers used as solvents was investigated. The aim was to gain access to the kinetics of the anionic ring-opening polymerization (AROP) of EO by an online and in-situ real-time method and to test alternative "greener" solvents in comparison to the well-established solvents, e.g. tetrahydrofuran (THF). For this purpose, we chose two promising "green" ethers, methyl tetrahydrofuran (MeTHF) and cyclopentyl methyl ether (CPME), with improved properties regarding reduced peroxide formation, higher boiling points, easier drying, and lower water solubility. During the AROP in the custom-built setup, in-situ IR measurements were performed and the final products were characterized by SEC, MALDI-TOF-MS, and 1 H NMR measurements, as well as newly in-house developed liquid chromatography (LC) investigations for purity analysis and diol impurity content estimations. Results presented in this study show that the controlled polymerization of EO in the tested alternative solvents represents a viable alternative to commonly established ones, as based on our kinetic studies and product characterization results. Graphical abstract: Highlights: Green ethers as solvent alternatives are compared to classical solvent THF for polymerization of ethylene oxide (EO). In-situ kinetic studies by online FTIR measurements. Characterization by SEC, MALDI-TOF-MS, and 1 H NMR measurements. LC investigations for purity analysis and diol impurity content estimations.